LISTENING TO UNLIMITED MUSIC: PEOPLE'S PERSPECTIVES ON WILLINGNESS TO PAY FOR PREMIUM USING SPOTIFY IN INDONESIA - Pawestri, Meidi Kalvina Dwi; Alfansi , Lizar (Finansha: Journal of Sharia Financial Management, 2025)
This study examines the psychological determinants that shape consumers’ willingness to pay for Spotify Premium in Indonesia. It investigates how the need for closure influences willingness to pay, with deal proneness tested as a moderating variable, and explores how self-brand connection affects willingness to pay through intransigent brand attitude. Data were collected from 220 active Spotify Premium users and analyzed using Structural Equation Modeling (SEM) with SmartPLS. The results reveal that the need for closure positively influences willingness to pay, whereas deal proneness does not moderate this relationship. Additionally, self-brand connection strongly enhances intransigent brand attitude, which in turn mediates its effect on willingness to pay. These findings highlight that psychological motivations and emotional brand attachment are key drivers of premium service adoption. Theoretically, this study contributes to the literature by integrating cognitive and affective constructs—need for closure, deal proneness, and self-brand connection—into a unified model situated within the Indonesian digital market context. Practically, the results offer strategic implications for digital marketers, suggesting that strengthening emotional engagement and identity-based branding may be more effective for increasing user loyalty and willingness to pay than relying solely on short-term promotional strategies.